2015
DOI: 10.1007/s11481-015-9614-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and T Lymphocytes: An Entangled Story

Abstract: Multiple sclerosis (MS) is the prototypic inflammatory disease of the central nervous system (CNS) characterized by multifocal areas of demyelination, axonal damage, activation of glial cells, and immune cell infiltration. Despite intensive years of research, the etiology of this neurological disorder remains elusive. Nevertheless, the abundance of immune cells such as T lymphocytes and their products in CNS lesions of MS patients supports the notion that MS is an immune-mediated disorder. An important body of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 262 publications
(338 reference statements)
3
104
0
3
Order By: Relevance
“…As seen in humans, certain behavioral changes can be observed in EAE mice (Acharjee et al, 2013; Franco-Pons et al, 2007; Jones et al, 2008; Legroux and Arbour, 2015; Moore et al, 2014; Serra-de-Oliveira et al, 2015; Ulrich et al, 2010; Wang et al, 2013). Clinical signs and paralysis in EAE mice are scored on a scale from 0 (clinically normal) to 5 (moribund) (Miller et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As seen in humans, certain behavioral changes can be observed in EAE mice (Acharjee et al, 2013; Franco-Pons et al, 2007; Jones et al, 2008; Legroux and Arbour, 2015; Moore et al, 2014; Serra-de-Oliveira et al, 2015; Ulrich et al, 2010; Wang et al, 2013). Clinical signs and paralysis in EAE mice are scored on a scale from 0 (clinically normal) to 5 (moribund) (Miller et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…The mounting evidence suggests that T helper 1 (Th1) and T helper 17 (Th17) cells are the main immunological players, resulting in experimental autoimmune encephalomyelitis (EAE) and MS (Babaloo et al, 2015; Hofstetter et al, 2009; Legroux and Arbour, 2015; Liu et al, 2014; Platten et al, 2009; Tzartos et al, 2008; Wang et al, 2009). Th1 cells, however, migrate across the blood-brain barrier into the CNS less efficiently than Th17 cells (Kebir et al, 2007; Marwaha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both MS and the murine model of the disease, experimental autoimmune encephalomyelitis (EAE), are believed to be primarily Th1 and T-helper type-17 (Th17)-mediated [17, 18]. Utilizing an adjuvant initially developed for protective vaccination against foreign pathogens, incomplete Freund’s adjuvant (IFA), studies have shown a shift from an autoantigen-specific Th1/Th17 towards a Th2/humoral response resulting in the suppression of autoimmune disease in animals [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…MS is considered the prototype [2] of IDD and affects over 2 million people worldwide [3]. The main manifestations of MS are transient and recurrent bouts of handicap[2], affecting mostly young adults with a strong sex bias of female to male about 4:1 [4], but the molecular mechanisms of IDD are essentially unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Complex interactions between genetic and environmental factors play key roles in the inflammatory process of the diseases [2] or influence the susceptibility to these diseases [5]. Many lines of clinical and experimental evidence have shown the involvement of the immune system in IDD, especially MS [6].…”
Section: Introductionmentioning
confidence: 99%